Engineering of core promoter regions enables the construction of constitutive and inducible promoters in Halomonas sp. Issue 2 (25th November 2015) - Li, Tingting; Li, Teng; Ji, Weiyue; Wang, Qiuyue; Zhang, Haoqian; Chen, Guo‐Qiang; Lou, Chunbo; Ouyang, Qi
Abstract: Halomonas strain TD01, a newly identified halophilic bacterium, has proven to be a promising low‐cost host for the production of chemicals. However, genetic manipulation in Halomonas sp. is still difficult due to the lack of well‐characterized and tunable expression systems. In this study, a systematic, efficient method was exploited to construct both a constitutive promoter library and inducible promoters. Porin, a highly expressed protein in Halomonas TD01, was first identified from the Halomonas TD01 proteome. Subsequent study of the intergenic region upstream of porin led to the identification of a core promoter region, including ‐10 and ‐35 elements. By randomizing the sequence between the ‐35 and ‐10 elements, a constitutive promoter library was obtained with 310‐fold variation in transcriptional activity; an inducible promoter with a >200‐fold induction was built by integrating a lac operator into the core promoter region. As two complementary expression systems, the constitutive and inducible promoters were then employed to regulate the biosynthetic pathway of poly‐3‐hydroxybutyrate (PHB) in Halomonas TD01, demonstrating the usefulness of the expression systems, furthermore, they could be applied in future metabolic engineering of Halomonas TD strains, and the systematic method used in this study can be generalized to other less‐characterized bacterial strains. Abstract : Halomonas TD01 is a halophilic strain with great potential in industrial production, especially in polyhydroxyalkanoates (PHAs) production. However, It is difficult to fine‐tune gene expressions in key metabolic pathways due to the lack of well‐characterized and tunable expression systems. In this work, a systematic investigation was exploited to conduct promoter identification and characterization, as well as a set of inducible and constitutive expression systems were constructed based on the identified core promoter. Finally, they were used to control the gene expressions of PHB synthesis. We believe that these expression systems could be used in other pathways engineering in Halomonas sp.